Preparation and Characterization of Water-Soluble Polymers and Their Utilization in Chromium Sorption - Sanchez-Poblete, J (John Wiley and Sons Inc., 2017)
In this article, we study the sorption of chromium from aqueous solutions using water-soluble polymers (WSPs): poly[2-(acryloyloxy) ethyl] trimethylammonium chloride, P(ClAETA); poly[2-(methacryloyloxy) ethyl] trimethylammonium methyl sulfate, P(SAETA); and poly(sodium 4-styrenesulfonate), P(NaSS). These WSPs were obtained by radical polymerization and purified by fractionation through ultrafiltration membranes with different molar mass cut-offs (30 and 100 kDa). The characterization was carried out by thermogravimetric analysis (TGA), FTIR, and 1H-NMR spectroscopies and scanning electron microscopy/energy dispersive X-ray spectroscopy. The chromium retention properties of the polymers were determined in terms of pH, optimal polymer concentration, and the effect of interfering ions. The results show yields above 80% for all of the synthesized WSPs. Characterization by spectroscopy confirmed the chemical structure of the polymers. TGA shows thermal decomposition temperatures of 264 and 324 °C for P(ClAETA) and P(SAETA), respectively. In the case of P(NaSS), the first thermal decomposition begins at approximately 450 °C. Maximum retention of Cr(VI) (100%) by the polymers P(ClAETA) and P(SAETA) was achieved at pH 9, and the maximum retention of Cr(III) (100%) was achieved by P(NaSS) at pH 3. The optimal polymer:Cr molar ratio obtained was 20:1. The retention of chromium(VI) was decreased by the presence of interfering ions, and the hydrodynamic flux was almost constant during ultrafiltration. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45355. © 2017 Wiley Periodicals, Inc.